Introducing phonetics and phonology - Davenport, Michael, 1954-; Hannahs, S. J. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Intended for the absolute beginner, Introducing Phonetics and Phono logy requires no previous background in linguistics, phonetics or phono logy. Starting with a grounding in phonetics and phonological theory, t he book provides a base from which more advanced treatments may be appr oached. It begins with an examination of the foundations of articulator y and acoustic phonetics, moves on to the basic principles of phonology , and ends with an outline of some further issues within contemporary p honology. Varieties of English, particularly Received Pronunciation and General American, form the focus of consideration, but aspects of the phonetics and phonology of other languages are discussed as well. This new edition includes: revised exercises and examples; additional covera ge of typology, autosegmental phonology, and articulatory and acoustic phonetics; broader coverage of varieties that now features Australian E nglish; and an extended chapter 7 that includes more information on the relationship between phonetics and phonology. Introducing Phonetics an d Phonology 4th Edition remains the essential introduction for any stud ents studying this topic for the first time. This new edition has been revised and updated throughout in light of advances in the field, witho ut compromising the overall aims of the text: to provide an accessible introduction to phonetics and phonology"--
Previous edition: London: Hodder Education, [2010].
Includes bibliographical references and index.
Keywords: Phonetics; Grammar, Comparative and general -- Phonology